PENGEMBANGAN MODUL EDUKASI KELUARGA ANAK JALANAN DI KAWASAN HARAPAN RAYA PEKANBARU - Sofiah Sofiah; Elni Yakub; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to develop and education module to families of street children in Harapan Raya area Pekanbaru, as seen from its’ validity. The research method used is research and development with reference to the flow of R & D steps, namely: potential problems, gethering collection, product design, design validation, design revision and product making. The instruments used was the assessments scale sheet, which was validated by 4 material expert, two guidence and counseling lectures and two guidance and counseling teacher. The results showed that the education module to families of street children developed is a good and valid category.Key Words: Education Module, Research & Development, Families Of Street Children